Interface immobilization chemistry of cRGD-based peptides regulates integrin mediated cell adhesion - Pallarola, Diego; Bochen, Alexander; Boehm, Heike; Rechenmacher, Florian; Sobahi, Tariq R.; Spatz, Joachim P.; Kessler, Horst (Advanced functional materials, 2014)
The interaction of specific surface receptors of the integrin family with different extracellular matrix-based ligands is of utmost importance for the cellular adhesion process. A ligand consists of an integrin-binding group, here cyclic RGDfX, a spacer molecule that lifts the integrin-binding group from the surface and a surface anchoring group. c(-RGDfX-) peptides are bound to gold nanoparticle structured surfaces via polyproline, polyethylene glycol or aminohexanoic acid containing spacers of different lengths. Although keeping the integrin-binding c(-RGDfX-) peptides constant for all compounds, changes of the ligand's spacer chemistry and length reveal significant differences in cell adhesion activation and focal adhesion formation. Polyproline-based peptides demonstrate improved cell adhesion kinetics and focal adhesion formation compared with common aminohexanoic acid or polyethylene glycol spacers. Binding activity can additionally be improved by applying ligands with two head groups, inducing a multimeric effect. This study gives insights into spacer-based differences in integrin-driven cell adhesion processes and remarkably highlights the polyproline-based spacers as suitable ligand-presenting templates for surface functionalization.
Published online: October 16, 2013
Gesehen am 21.10.2020